Lignin solubilisation and gentle fractionation in liquid ammonia. Issue 1 (18th September 2014) - Strassberger, Zea; Prinsen, Pepijn; Klis, Frits van der; Es, Daan S. van; Tanase, Stefania; Rothenberg, Gadi
Abstract : It's definitely not water! The complete dissolution of lignin in pure liquid ammonia opens opportunities for converting this abundant yet stubborn biopolymer to useful aromatics under moderate conditions. Abstract : We present a simple method for solubilising lignin using liquid ammonia. Unlike water, which requires harsh conditions, ammonia can solubilise technical lignins, in particular kraft lignin. A commercial pine wood Kraft lignin (Indulin AT) was solubilized instantaneously at room temperature and 7–11 bars autogeneous pressure, while a commercial mixed wheat straw/Sarkanda grass soda lignin (Protobind™ 1000) was solubilized within 3 h at ambient temperature, and 30 min at. 85 °C. Hydroxide salts were not required. Wheat straw, poplar and spruce organosolv lignins, as well as elephant grass native lignin (MWL) were also solubilized, albeit at lower values. Different sequences of solubilisation and extraction were tested on the Protobind™ 1000 lignin. The remaining lignin residues were characterized by FTIR, size exclusion chromatography (SEC), elemental analysis (ICP), 2D-NMR and 31 P NMR. Liquid ammonia is not an innocent solvent, as some nitrogen was incorporated in the residual lignin which then rearranged to higher molecular weight fractions. Nevertheless, the mild solubilisation conditions make liquid ammonia an attractive candidate as a solvent for lignin in future biorefinery processes.